Rhetoric in lessons of english in vocational progremmes of upper secondary education - Makovecki, Nataša (Šolsko polje, 2007)
The paper presents experiences of including rhetorical topics in English lessons in two three-year vocational programmes at the School Centre in Velenje over the period of five years. Teaching English in these programmes faces specific problems which need to be considered in lesson plans. The most critical ones are: lack of motivation and self-reliance, poor self-image, problems with discipline and a very limited linguistic competence and poor speaking skills in a foreign language (and the mother tongue). The methodological approach was based upon tree principles: usefulness (applicability), concreteness (inductive approach) and shortness (less is more). The paper presents some of the used methods: presenting theory with illustrative examples, execution of oral exercises in the form of discussion groups and preparation of a two-minute oral presentation on a chosen topic by the students. This approach increased the students' motivation and put them into a more active role in the learning process. They learned how to use arguments to channel criticism and emotions into language. It encouraged the students' awareness of taking the responsibility for themselves and others.
Keywords: angleški jezik; kritično mišljenje; poklicno izobraževanje; pouk; retorika; učenje